Estradiol and progesterone regulate the migration of mast cells from the periphery to the uterus and induce their maturation and degranulation - Jensen, Federico (2010)
Background: Mast cells (MCs) have long been suspected as important players for implantation based on the fact that their degranulation causes the release of pivotal factors, e.g., histamine, MMPs, tryptase and VEGF, which are known to be involved in the attachment and posterior invasion of the embryo into the uterus. Moreover, MC degranulation correlates with angiogenesis during pregnancy. The number of MCs in the uterus has been shown to fluctuate during menstrual cycle in human and estrus cycle in rat and mouse indicating a hormonal influence on their recruitment from the periphery to the uterus. However, the mechanisms behind MC migration to the uterus are still unknown. Methodology/Principal Findings: We first utilized migration assays to show that MCs are able to migrate to the uterus and to the fetal-maternal interface upon up-regulation of the expression of chemokine receptors by hormonal changes. By using a model of ovariectomized animals, we provide clear evidences that also in vivo, estradiol and progesterone attract MC to the uterus and further provoke their maturation and degranulation. Conclusion/Significance: We propose that estradiol and progesterone modulate the migration of MCs from the periphery to the uterus and their degranulation, which may prepare the uterus for implantation.